Development and evaluation of a new real‐time RT‐PCR assay for detecting the latest H9N2 influenza viruses capable of causing human infection. (30th January 2019) - Saito, Shinji; Takayama, Ikuyo; Nakauchi, Mina; Nagata, Shiho; Oba, Kunihiro; Odagiri, Takato; Kageyama, Tsutomu
Abstract: The H9N2 subtype of avian influenza A viruses (AIV) has spread among domestic poultry and wild birds worldwide. H9N2 AIV is sporadically transmitted to humans from avian species. A total of 42 laboratory‐confirmed cases of non‐fatal human infection with the Eurasian Y280 and G1 lineages have been reported in China, Hong Kong, Bangladesh and Egypt since 1997. H9N2 AIV infections in poultry have become endemic in Asia and the Middle East and are a major source of viral internal genes for other AIV subtypes, such that continuous monitoring of H9N2 AIV is recommended. In this study, a new, one‐step, real‐time RT‐PCR assay was developed to detect two major Eurasian H9 lineages of AIV capable of causing human infection. The sensitivity of this assay was determined using in vitro ‐transcribed RNA, and the detection limit was approximately 3 copies/reaction. In this assay, no cross‐reactivity was observed against RNA from H1–15 subtypes of influenza A viruses, influenza B viruses and other viral respiratory pathogens. In addition, this assay could detect the H9 hemagglutinin (HA) gene from artificially reconstituted clinical samples spiked with H9N2 virus without any non‐specific reactions. Therefore, this assay is highly sensitive and specific for H9 HA detection. The assay is useful both for diagnostic purposes in cases of suspected human infection with influenza H9N2 viruses and for the surveillance of both avian and human influenza viruses.